(untitled) (Journal of Economic Research & Business Administration, 2017)
The article describes the features of the development of the innovation process in Kazakhstan companies, made an analysis of the development of innovative activity in the Republic of Kazakhstan, formulated the main problems hindering the development of innovative entrepreneurship. Also in this paper we consider the experience of foreign countries and organizations to support innovative activities, recommendations for the development of innovative strategies for the enterprise. Permanent and continuous creation and implementation of innovations is the main factor of succeeding in the competition of any enterprise, region and country as a whole. Implementation of novelty, innovation, and new scientific and technological achievements in the production of new products, technologies and services is crucial for the development of the national economy and raising the living standards of the population. In order for constantly improvement of welfare level, it is necessary to continuously improve and transform the products, services, improve production and management functions on the basis of innovation and innovative technologies. Competitive advantage on the market now have countries that provide long-term strategy of innovative development, aimed at various market needs.